2019
DOI: 10.3390/w11010098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Wind Velocity and Soil Moisture Condition on Soil Erosion in Andosol Agricultural Fields (Model Experiment)

Abstract: Soil erosion by the wind is an important phenomenon in drastic soil degradation. In Japan, andosol agricultural field is eroded by the wind and agricultural productivity is significantly affected. The aim of this study was to evaluate the effect of wind velocity and soil moisture condition on the soil erosion in andosol agricultural fields. Also, we determined the timing and amount of irrigation water needed to prevent soil erosion by the wind with respect to the wind and soil moisture conditions. A numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, the factors that control the threshold wind speed of dust release are diverse 1,2 . For example, soil moisture is one of the most important factors for dust entrainment threshold 5456 . Moisture should therefore be considered for estimating dust release in very sparsely vegetated land by applying our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, the factors that control the threshold wind speed of dust release are diverse 1,2 . For example, soil moisture is one of the most important factors for dust entrainment threshold 5456 . Moisture should therefore be considered for estimating dust release in very sparsely vegetated land by applying our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the work of Uzun et al (2017), who reported the force required to separate soil particles to be greater at higher soil moisture content under the action of water in the film between the soil particles. Under wet conditions, the tension between water molecules and soil particles in the soil increases the cohesion between the particles, and thus an increase in soil moisture content enhances the cohesion and agglomeration of the soil, which ultimately increases the starting wind speed of the soil (Yuge and Anan, 2019;Wang et al, 2021). Therefore, when soil moisture content is high, it is difficult for soil particles to move even if the wind reaches the starting wind speed of the soil particles.…”
Section: Tillage Treatmentmentioning
confidence: 99%